Religion and the Conceptual Boundary in Central and Eastern Europe Encounters of Faiths - Bremer, T.; Bremer, T. (Studies in Central and Eastern Europe, 2008)
This volume concentrates on the 'conceptual boundary' through Europe which is determined by Western and Eastern Christianity. The chapters show that the boundary has never been a stable and defined division, but that it was also subject to change and development and a place of encounter and exchange between religions and cultures.